Identifying Student Misconceptions in Thermodynamics Material - Rahmadani, Dea; Angraini, Rini; Fitria, Tazha Eka (Universitas Mandiri, 2025)
This study aims to identify students' misconceptions in studying thermodynamics. This test includes (1) identifying whether students have misconceptions or not, (2) determining the part of the material where students have misconceptions, and (3) revealing the factors that cause these misconceptions. This study uses a literature review method by analyzing 15 articles and theses as samples. Data were collected through collecting scientific articles and theses that have similar topics related to students' misconceptions in thermodynamics, which were then analyzed. The results of the study showed that several misconceptions were found related to the concepts of work, heat, and energy in the system, thermodynamic processes such as isobaric, isochoric, and isothermal, the laws of thermodynamics, and quantitative interpretations such as PV diagrams. The factors causing these misconceptions are in-depth understanding, abstract nature of the material, lack of practical experience, ineffective teaching methods, and the use of inaccurate textbooks. To overcome this problem, diagnostic methods such as three-level diagnostic tests, clinical interviews, and interactive teaching efforts are considered important in identifying and correcting misconceptions.